Neurofilament light chain in central nervous system infections: a prospective study of diagnostic accuracy - van Zeggeren, Ingeborg E.; ter Horst, Liora; Heijst, Hans; Teunissen, Charlotte E.; van de Beek, Diederik; Brouwer, Matthijs C. (Scientific reports, 2022)
Diagnosing central nervous system (CNS) infections quickly is often difficult. Neurofilament light chain (NfL) is a component of the axonal cytoskeleton and identified as marker of neuronal damage in several CNS diseases. We evaluated the diagnostic accuracy of NfL for diagnosing CNS infections. We included patients from a prospective cohort of consecutive patients in whom a lumbar puncture was performed for suspected CNS infection in an academic hospital in The Netherlands. The index test was NfL in cerebrospinal fluid (CSF) and reference standard the final clinical diagnosis. Diagnostic accuracy was determined using the area-under-the-curve (AUC) with 95% confidence intervals (CI). The association of CSF NfL with clinical characteristics, diagnosis and outcome was evaluated. Between 2012 and 2015, 273 episodes in adults of which sufficient CSF was available were included. CNS infection was diagnosed in 26%(n = 70), CNS inflammatory disease in 7%(n = 20), systemic infection in 32%(n = 87), and other neurological disorders in 33%(n = 90). Median CSF NfL level was 593 pg/ml (IQR 249–1569) and did not discriminate between diagnostic categories or CNS infection subcategories. AUC for diagnosing any CNS infection compared to patients without CNS infections was 0.50 (95% CI 0.42–0.59). Patients presenting with an altered mental status had higher NfL levels compared to other patients. We concluded that NfL cannot discriminate between causes in patients suspected of CNS infections. High concentrations of NfL are associated with severe neurological disease and the prognostic value of NfL in patients with CNS infections should be investigated in future research.